Multiple myeloma and pulmonary aspergillosis: dental treatment prior to chemotherapy and management of post extraction complications. Issue 4 (15th April 2020) - Patrick, Amy; Saeed, Khadeeja; Kumar, Navdeep
Abstract : This case study discusses the dental management of a patient with a history of multiple myeloma and pulmonary aspergillosis, whom was referred to a hospital-based dental service for urgent dental review. The patient had received a dental assessment in primary care prior to commencement of chemotherapy and had four teeth extracted without complications. However, following the commencement of chemotherapy, he presented with a significant infection associated with two of his wisdom teeth resulting in extraction. Despite atraumatic extraction, the upper right wisdom tooth socket developed an oroantral fistula. A multidisciplinary team approach was required to enable effective patient management in this complex patient regarding myeloma, aspergillosis and the medications used including bisphosphonates and chemotherapy. It highlights the higher risk of oral complications that can arise in myelosuppressed patients and emphasises the need to identify potential sources of dental infection prior to the commencement of chemotherapy.